Compositermes vindai (Isoptera: Termitidae: Apicotermitinae), a new genus and species of soldierless termite from the Neotropics - Scheffrahn, Rudolf H. (Zootaxa, 2013)
The New World Anoplotermes group is a common and diverse clade of soil-dwelling soldierless termites that is undergo-ing needed taxonomic reclassification. Based on robust worker gut morphology centered near the enteric valve, a new ge-nus and its singular species, Compositermes vindai, are described from collections encompassing a massive expanse of tropical America. The enteric valve armature is thought to enhance inoculation of the food stream with symbiotic bacteria.